Giant Enhancement of Second Harmonic Generation Accompanied by the Structural Transformation of 7‐Fold to 8‐Fold Interpenetrated Metal–Organic Frameworks (MOFs). Issue 2 (23rd October 2019) - Chen, Zhihui; Gallo, Gianpiero; Sawant, Vaishali A.; Zhang, Tianxiang; Zhu, Menglong; Liang, Liangliang; Chanthapally, Anjana; Bolla, Geetha; Quah, Hong Sheng; Liu, Xiaogang; Loh, Kian Ping; Dinnebier, Robert E.; et al.
Abstract: Interpenetration in metal–organic frameworks (MOFs) is an intriguing phenomenon with significant impacts on their properties, and functional applications. Herein, we show that a 7‐fold interpenetrated MOF (1 ) is transformed into an 8‐fold interpenetrated MOF by the loss of DMF in a single‐crystal‐to‐single‐crystal manner. This is accompanied by a giant enhancement of the second harmonic generation (SHG ca. 125 times) and two‐photon photoluminescence (ca. 14 times). The strengthened π–π interaction between the individual diamondoid networks and intensified oscillator strength of the molecules aid the augment of dipole moments and boost the nonlinear optical conversion efficiency. Large positive and negative thermal expansions of 1 occur at 30–150 °C before the loss of DMF. These results offer an avenue to manipulate the NLO properties of MOFs using interpenetration and provide access to tunable single‐crystal NLO devices. Abstract : Improved by interpenetration : A 7‐fold to an 8‐fold transformation of MOFs by the loss of DMF is accompanied by a giant enhancement of the second harmonic generation (SHG) and two‐photon emission facilitated by the increased π–π interaction and oscillator strength. Thus the nonlinear optics (NLO) properties of MOFs can be manipulated using interpenetration.